ENVIRONMENTAL AND HEALTH RISK ASSESSMENT (EHRA) APPROACHES IN THE STRATEGIC ENVIRONMENTAL RISK ASSESSMENT (SEA) : A METAANALYSIS - Anindrya Nastiti; Siska Widya D Kusumah; Mariana Marselina; Karina Nursyafira; Astrid Monica; Dharmawan Phan (Universitas Trisakti, 2020)
Aim: This paper aims to understand how the concept of risk and riskgovernance can be best articulated and integrated into Indonesia’s SEA.Attention regarding health risks emerging from human interactions withthe physical environment has increased in Sustainable Development andPlanning (SDP). Methodology and Results: Strategic EnvironmentAssessment (SEA) is the current context-based methodology addressingenvironmental and health risks of development planning in manycountries. Environmental and health risk assessment (EHRA) is anintegrated part of the SEA. EHRA, as a field of science, has evolved towardsspecific needs in many sectors, e.g. dose-response, quantitative microbialrisk assessment, ecological risk assessment. The main challenge is how todetermine the suitable EHRA approaches and translate the fact-basedEHRA into risk-informed strategies in SDP. In Indonesia, the SEA is mandatory for regional planning documents. However, there is limitedguidelines and application on EHRA in SEA. Through a meta-analysis, wereviewed scholarly articles published from 2009 to 2019 available inGoogle Scholar that report the concepts and implementation of EHRA andSEA in various countries. Conclusion, significance and study impact: Thisstudy has significant implications for the understanding of risk governancein SDP.